2014
DOI: 10.1080/15299716.2014.933378
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Sexual Orientation Range and Why It's Worth Measuring

Abstract: First proposed by Epstein, McKinney, Fox, and Garcia (2012), sexual orientation range (SOR) is an objective continuous measure of the flexibility people have in expressing their sexual orientation. In the present article, three formulas for computing SOR are compared using data obtained from a sample of 54,834 people in 57 countries. A number of statistical measures suggest that SOR is best measured simply as the smaller of two raw scores indicating opposite-sex and same-sex sexual inclinations. In other words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
4
8
0
Order By: Relevance
“…The sexual behavior and identity measures were the most highly criticized, with participants pointing out that definitions of terms such as "heterosexual" and "homosexual" are not clear in a context where people are shifting their gender expression and secondary sex characteristics and some individuals do not identify with the gender binary. This feedback is consistent with previous research with sexual minorities, which has highlighted the challenges of measuring sexual orientation in an inclusive and sensitive manner (Epstein & Robertson, 2014;Weinrich, 2014). However, more work is needed to understand the best approaches to measuring sexual orientation among transgender individuals.…”
Section: Discussionsupporting
confidence: 90%
“…The sexual behavior and identity measures were the most highly criticized, with participants pointing out that definitions of terms such as "heterosexual" and "homosexual" are not clear in a context where people are shifting their gender expression and secondary sex characteristics and some individuals do not identify with the gender binary. This feedback is consistent with previous research with sexual minorities, which has highlighted the challenges of measuring sexual orientation in an inclusive and sensitive manner (Epstein & Robertson, 2014;Weinrich, 2014). However, more work is needed to understand the best approaches to measuring sexual orientation among transgender individuals.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study found that approximately 10% of individuals could not be categorized in a study using three categories (lesbian, gay, and bisexual) because they identified as something other than LGB or heterosexual (Korchmaros, Powell, & Stevens, 2013). Other researchers have argued that because of its fluidity and flexibility, sexual orientation is not a categorical phenomenon and should be measured as a range that takes into account heterosexual and LGB aspects of a person (Epstein & Robertson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Future research areas include but are not limited to LGBTQ+-specific risk and protective factors, LGBTQ+-affirming evidence-based practices and treatment strategies, addiction and offender counselor competence to treat LGBTQ+ clients, and SUDs' and process addictions' influence in the lives of LGBTQ+ individuals across the life span. Second, addiction researchers should consider evolving how they think about sexual orientation and gender identity in research from categorical constructs to continuous facets of identity and should adapt how these demographic characteristics are assessed in research (Epstein & Robertson, 2014). If essentialist categories of sexual orientation and gender identity must be used in a particular study, researchers may obtain more accurate results by not oversimplifying LGBTQ+ identities and by providing nonbinary options with which participants may identify (Beaulieu-Prévost & Fortin, 2015;Flentje, Bacca, & Cochran, 2015).…”
Section: Implications For Researchmentioning
confidence: 99%
“…Because prior sexual experiences might have influenced participant's responses to the olfactory prime, participants were asked about such experiences over the past year on a 4-point Likert scale. (Researchers who examine sexual orientation have come to regard it as not a categorical variable; that is, same-sex and opposite-sex inclinations appear in virtually everyone at some point in their lives in different degrees and proportions [see Epstein & Robertson, 2014; This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Methodsmentioning
confidence: 99%